137 Utility of MMG (Mechanomyography) on Intraoperative Clinical Decision Making in Peripheral Nerve Surgery. (1st April 2022) - Guerrero, Jaime; Javeed, Saad; Dibble, Christopher; Ray, Zack; Faraji, Amir H.
Abstract : INTRODUCTION: Recent studies demonstrated the high sensitivity of mechanomyography (MMG) as a novel minimally invasive technique in detecting nerve function as compared to traditional electromyographic recording. MMG reflects the mechanical vibrations of single motor units detected via accelerometer sensors. We hypothesize that MMG will be a powerful intraoperative tool to supplement traditional nerve diagnostic and imaging methodologies. METHODS: We utilized the Sentio MMG system (Depuy-Synthes) to monitor nerve function during surgical decompression of chronic cubital tunnel and peroneal nerve entrapment. Accelerometer sensors were placed on target myotomes. Intraoperatively, the nerves were stimulated at a 0.1 mA threshold, with 0.1 mA increases until muscle activity was noted. The final threshold current was recorded prior to decompression and following decompression. RESULTS: A total of four patients were included in this initial report. Intraoperatively, MMG stimulus thresholds were recorded in all four patients prior to decompression at 1.5 ± 0.1 mA. Following proximal decompression, immediate improvements in MMG stimulus thresholds were noted. Following distal decompression, the final stimulus thresholds were noted at 0.5 ± 0.1 mA (p = 0.0001, one-way ANOVA). Postoperatively, all patients endorsed symptomatic improvement in pain and motor strength. This data is preliminary and continued enrollment and long term follow up is currently underway. CONCLUSION: MMG is a sensitive technique that is readily adoptable in standard workflows. Importantly, MMG stimulus thresholds may provide objective guidance within intraoperative decision making in determining the extent of surgical decompression. Future work should focus on validating normative values of MMG stimulus thresholds in various nerves and establishing clinical associations with functional outcomes.